Integrating Ngadhu Bhaga oral traditions into elementary school learning materials - Awe, Ermelinda Yosefa; Noge, Maria Desidaria; Ciak, Maria Sintia (Jurnal Prima Edukasia, 2026)
This study aims to analyze the forms of oral traditions and values of the surviving Ngadhu Bhaga ethnic oral traditions at Ngada Regency that could potentially be used as learning materials in elementary schools. The method used is a case study with a qualitative approach. The data collection was conducted through observation, in-depth interviews with traditional figures, the Education and Culture Office, and documentation. Data analysis uses Campbell's model with a concept-setting approach. Research results show that the Ngadhu Bhaga ethnic oral tradition is still widely found in folktales, myths, legends, and pantuns, and has a potential cultural wealth to be used as contextual learning material. Values such as cooperation, respect, responsibility, and local wisdom are contained in the tradition and are highly relevant to instilling them in students early on. The oral traditions acquired in this study are Inerie folklore, Bu'e Wio folklore, Watu Kaba story, Wolo Watu Ata story, Ngadhubhaga myth or ancestral travel legend, and Ngadhubbhaga traditional proverbs. Stories – these stories and proverbs contain high values that are highly relevant to strengthening student character, and also serve as a form of preservation of local culture in elementary schools. This study recommends that this form of oral tradition be integrated into Indonesian, PPKn, IPS, and also the Art of Culture.